On Strategic Enabling of Product Piracy in the Market for Video Games - Oliver Gürtler (University of Bonn, Bonn Graduate School of Economics (BGSE), 2005)
In this paper, we consider the market for video games, where some firms are active in both, the market for video games hardware and software. It is puzzling that hardware can be easily made compatible with duplicated (i.e. pirated) software. We ask, whether there exist strategic reasons explaining this puzzle. Firms may, for example, enable software piracy in order to increase their market shares in the hardware market. This will indeed be true, if hardware prices are fixed and the market is completely covered. With endogenous prices, however, price reactions to enabling of product piracy will offset the increase in market shares and copy protection will be set at the highest possible level. If, on the other hand, the market is only partially covered, copy protection will be strategically reduced. In doing so, hardware firms shift reservation prices from the software to the more important hardware market.
Keywords: D21; L86; L13; 330; Video Games Market; Product Piracy; Fundamental Transformation